The Extended vs. The Modern Synthesis of Evolutionary Theory - Sergio Da Silva (Philosophies, 2025)
This paper examines the extended evolutionary synthesis’s critique of the modern synthesis, and introduces the “survival of the luckiest” framework as a mediating perspective. This framework preserves the core principles of the modern synthesis, while incorporating an additional element of randomness arising from the interplay of natural and sexual selection. Although the extended synthesis emphasizes developmental processes, niche construction, epigenetic inheritance, and horizontal gene transfer, it also neglects the critical role of this additional randomness. By critically analyzing the evidence provided by proponents of the extended synthesis, we show that the survival of the luckiest framework offers compelling alternative explanations. In doing so, it bridges the modern synthesis with principles of self-organization and emergence, addressing key gaps while maintaining its foundational tenets.